E-MODUL PEMBELAJARAN TERPADU DENGAN MODEL IMMERSED BERBASIS KEARIFAN LOKAL UNTUK MENINGKATKAN LITERASI BUDAYA SISWA SEKOLAH DASAR - Fitriyah, Siti Ni'matul; Supriyono; Rahayuningsih, Sri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Integrated learning is an approach to develop learners' ability to form knowledge based on interaction with the environment and experiences in their lives. The immersed model is designed to assist students in organizing and combining various experiences and knowledge related to their context of use. This study aims to improve students' cultural literacy skills through the E-module that has been developed. This research uses a quantitative method of quasi experiment type with one group pre-test post-test design. The sample in this study were fourth grade students of SDN Sumbersari 03 Malang City with 27 of students. Quantitative data were collected through pre and post tests using question instruments that have been designed and measured for validity and reliability (a = 0.972). Data analysis was conducted using Microsoft excel application to determine the t-statistic value and N-Gain Score. The average pre-test and post-test scores of students were 72.85 and 81.52 respectively, an average increase of 8.67 points. Meanwhile, the t-statistic value is 0.001 and the N-Gain Score is 32%. Thus the E-Module used in this study has been effective in improving the cultural literacy skills of elementary school students.